The African Open Access portal (AfricArXiv) as a Covid-19 information hub - Mensah, Priscilla; Ahmad, Umar Salisu; Okelo, Luke (My University, 2020)
Webinar presentation on Accelerating Reach and Discoverability of COVID-19 Related Research from and About Africa by Mr. Luke Okelo, Ms. Priscilla Mensah, and Dr. Umar Ahmad at the UNISA Open Access Webinar: Global Collaboration to Accelerate Transition to Open Access (http://uir.unisa.ac.za/handle/10500/26711) on October 21, 2020.
Keywords: AfricArXiv; COVID-19; Figshare; Open Access; Open Science Framework; PubPub; ScienceOpen; UNISA; Zonodo